2017
DOI: 10.1016/j.actbio.2017.01.048
|View full text |Cite
|
Sign up to set email alerts
|

Peptide and nucleic acid-directed self-assembly of cationic nanovehicles through giant unilamellar vesicle modification: Targetable nanocomplexes for in vivo nucleic acid delivery

Abstract: The efficient targeted delivery of nucleic acids in vivo provides some of the greatest challenges to the development of genetic therapies. Giant unilamellar lipid vesicles (GUVs) have been used mainly as cell and tissue mimics and are instrumental in studying lipid bilayers and interactions. Here, the GUVs have been modified into smaller nanovesicles. We have then developed novel nanovesicle complexes comprising self-assembling mixtures of the nanovesicles, plasmid DNA or siRNA, and targeting peptide ligands. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 67 publications
1
24
0
Order By: Relevance
“…They are suitable for hydrophobic compounds and may also override drug resistance mechanisms [30,31]. Nanoparticles are also known to take advantage of tumour vascular leakiness to more specifically access tumour cells in solid tumours including neuroblastoma [25,28,32]. For RAMBAs, this approach has not been documented to date and we hypothesised that liposomal delivery would improve bioavailability and making such compounds more accessible for use in humans.…”
Section: Introductionmentioning
confidence: 99%
“…They are suitable for hydrophobic compounds and may also override drug resistance mechanisms [30,31]. Nanoparticles are also known to take advantage of tumour vascular leakiness to more specifically access tumour cells in solid tumours including neuroblastoma [25,28,32]. For RAMBAs, this approach has not been documented to date and we hypothesised that liposomal delivery would improve bioavailability and making such compounds more accessible for use in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Grafting‐from Approach : In the grafting‐from approach, small initiator molecules are linked to a peptide/protein and polymerization is initiated by these macroinitiators . A drawback to this approach is that the polymerization technique should not be allowed to affect the activity of the peptides or the 3D structure of the proteins, which would otherwise lead to a denaturation of the protein . Considering this, Bontempo and Maynard conjugated biotinylated atom transfer radical polymerization (ATRP) to streptavidin (SAv) to develop a protein macroinitiator.…”
Section: Hybrid Vesicular Delivery Systemsmentioning
confidence: 99%
“…Tagalakis et al used giant unilamellar vesicle (GUV) precursors and targeting peptides to improve nucleic acid delivery. They demonstrated that biologically safe and stable nanovesicles were produced that were not cytotoxic and did not activate complement systems, unlike usual lipopolyplexes …”
Section: Hybrid Vesicular Delivery Systemsmentioning
confidence: 99%
“…8 The ideal non-viral vector should have the following characteristics: small size below 200 nm, biocompatible, stable enough in blood to protect the nucleic acid, effective delivery of gene into target location, and so on. 9 Selenium (Se) is a mineral trace element of fundamental importance to humans and animals. The role of Se in potential cancer chemotherapeutic and chemopreventive agents has been supported by many epidemiological, preclinical, and clinical studies.…”
Section: Introductionmentioning
confidence: 99%